Poisoning-related emergency department visits in children with autism spectrum disorder - Emma Cornell; Ashley Blanchard; Stanford Chihuri; Carolyn G. DiGuiseppi; Guohua Li (Injury Epidemiology, 2022)
Abstract Background Autism spectrum disorder (ASD) is a complex neurodevelopmental condition, and its prevalence has increased markedly in the past two decades. Research indicates that people with ASD are at increased risk for premature mortality from injuries. Often, children with ASD are prescribed multiple medications, increasing their risk for intentional and unintentional poisonings. We examined the epidemiologic patterns of emergency department (ED)-treated poisonings in children with ASD and the association of ED-treated poisonings with ASD according to common co-occurring conditions. Methods We analyzed data from the Nationwide Emergency Department Sample for 2016–2018 to estimate the frequencies of ED-treated poisonings among autistic children aged 1–20 years and adjusted odds ratios of ED-treated poisoning associated with ASD in the presence or absence of co-occurring attention-deficit hyperactivity disorder (ADHD) or intellectual disability (ID). The ICD-10-CM external cause-of-injury matrix was utilized to identify poisoning cases. Results During 2016–2018, there were an estimated 523,232 ED visits in children with ASD aged 1–20 years, including 12,152 (2.3%) visits for poisoning. Of ED-treated poisonings in children with ASD, 73.6% were related to pharmaceutical drugs, such as psychotropic medications and prescription opioids, 16.6% were intentional, 36.5% were unintentional, and 47.0% were undetermined. Among children with ASD, those aged 5–9 had the highest odds of poisoning-related ED visits compared to all other age-groups (adjusted OR = 3.41; 95% CI 3.15, 3.68). The odds of poisoning for children with ASD were 59.0% greater than for their peers (adjusted OR = 1.59; 95% CI 1.53, 1.66) and varied significantly with age and co-occurring ADHD or ID. Conclusions Children with ASD are at a significantly increased risk of poisoning, particularly among those aged 5–9 years. Co-occurring ADHD or ID with ASD further increases the risk of poisoning. Interventions to reduce poisoning in children with ASD should prioritize the safety of prescription medications.